Operator formulation of q-deformed dual string model - Chaichian, M.; Gomes, J. F. [UNESP]; Kulish, P. (Elsevier, 1993)
We present an operator formulation of the q-deformed dual string model amplitude using an infinite set of q-harmonic oscillators. The formalism attains the crossing symmetry and factorization and allows to express the general n-point function as a factorized product of vertices and propagators.